2020
DOI: 10.3390/app10186370
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Induction Imaging with Atomic Magnetometers: Progress and Perspectives

Abstract: Electromagnetic induction imaging (EMI) allows mapping of the conductivity of target objects and, when combined with appropriate algorithms, the generation of full 3D tomographic images. Despite its tremendous potential, and the wealth of possible applications, the use of EMI has essentially been limited to eddy current testing for monitoring of corrosion and welding in metallic structures. The present work reviews the factors hindering the progress of electromagnetic induction imaging and highlights how the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Biomedical magnetomyography (MMG) [145,161], magnetoencephalography (MEG) [83,121,122,128,134,[162][163][164][165][166], (fetal) magnetocardiography (MCG and fMCG) [19,20,92,120,164,167], magnetic-field imaging (MFI) [168] magnetic biomarkers [124,[169][170][171][172] plant biomagnetism [173,174] Zero-/low-field NMR [125,126,139,[175][176][177][178][179]] Geophysics [85,180] Aerospace [102,181] Laser guide stars [182] Defense and industry underwater surveillance [135], electromagnetic induction imaging [183][184][185][186] Fundamental science search for new physics beyond particle standard model [38,76,…”
Section: Typical Applications Of Atomic Magnetometersmentioning
confidence: 99%
“…Biomedical magnetomyography (MMG) [145,161], magnetoencephalography (MEG) [83,121,122,128,134,[162][163][164][165][166], (fetal) magnetocardiography (MCG and fMCG) [19,20,92,120,164,167], magnetic-field imaging (MFI) [168] magnetic biomarkers [124,[169][170][171][172] plant biomagnetism [173,174] Zero-/low-field NMR [125,126,139,[175][176][177][178][179]] Geophysics [85,180] Aerospace [102,181] Laser guide stars [182] Defense and industry underwater surveillance [135], electromagnetic induction imaging [183][184][185][186] Fundamental science search for new physics beyond particle standard model [38,76,…”
Section: Typical Applications Of Atomic Magnetometersmentioning
confidence: 99%
“…Notably, a review paper highlighted the progress of electromagnetic induction imaging (EMI) with atomic magnetometers, indicating that EMI technology has entered a new phase of development with real-word applications now within reach. [10] Furthermore, AMAs are used in various applications, including the testing of magnetic materials, [11] functional magnetic imaging of humans, [12][13][14] monitoring of the Earth's magnetic field, [15] and detecting biomagnetic signals with high spatial resolution. [16] Researchers have emphasized that using a magnetometer with a single-beam setup effectively simplifies the optical paths by combining the pump and probe light into a single beam.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [4] demonstrated that electromagnetic induction imaging (EMI) with atomic magnetometers (AMs) [5]- [7] can identify and quantify localized thinning of metal plates, thus opening up an alternative viable route for imaging of corrosion under insulation. EMI-AMs is advantageous for CUI imaging with respect to existing techniques: it is simple and low cost, it does not involve ionising radiation, thus being completely harmless, and retains its capability at low frequency, which results in a significant penetrating power both through insulating material as well though the pipeline core structure.…”
Section: Introductionmentioning
confidence: 99%